Branding in the eye of the storm : the impact of brand ethical behavior on brand commitment during the COVID-19 crisis in a South American country (2023)
The purpose of this study is to determine how consumer perceptions of brand ethical behavior can affect their commitment to brands during turbulent times. A study of the effects of perceived ethical behavior of brands in Colombia during the initial months of the COVID-19 outbreak was conducted in May 2020 in Bogota, Colombia, to ascertain customer perception of brand ethical actions during the first 2 months of the COVID-19 outbreak. A Bayesian model was developed to assess the impact of brands' ethical behavior on brand recognition benefits, brand image, and brand commitment. The selection of the initial months of the outbreak for this project was important because the COVID-19 pandemic had the potential to augment consumer perception of brands' ethical actions at a pivotal moment in consumers' lives. Our findings demonstrate that customers expressed a positive perception of brands' ethical actions during the early months of the pandemic, which resulted in high commitment intention to these brands in the model examined. The findings highlight the critical nature of the perception of ethical behavior in the eyes of customers during a major global health crisis. More than ever, organizations must commit their brands to fully live out their publicly expressed ethical principles and continuously monitor consumer perceptions of brand attributes and behaviors associated with ethical actions regardless of market conditions. Commitment to living the brand's stated ethical principles can be demonstrated via branding activities in ways that can be especially welcomed by customers during turbulent times. The insights mentioned in this article are crucial for brands already present in South America or exploring expansion into these regions. The findings provide compelling evidence of the impact of ethical actions on consumer commitment to brands, suggesting that brands must now, more than ever, stay in touch with their customers and truthfully live the ethical values they transmit to customers.